Nondestructive and accurate prediction of IGBT junction temperature in wind power converters: based on IDMOA-ELM prediction method - Jiaqi, Liu; Li, Lingling; Liu, Yuwei (Nondestructive testing and evaluation, 2025)
This study has made significant advancements in predicting junction temperature of IGBTs in wind power converters. An improved dwarf mongoose optimisation algorithm (IDMOA) with superior performance was developed. The IDMOA improves the initial solution quality through Hammersley initialisation, balances global search and local optimisation with nonlinear dynamic decreasing weight factors, and enhances population diversity via differential evolution strategy to avoid local optima. The IDMOA optimizes random parameters of extreme learning machine (ELM), overcoming the limitations of traditional manual parameter setting and constructing a high-precision IDMOA optimised ELM (IDMOA-ELM) model. Simulation results indicate that the IDMOA-ELM excels in predicting the IGBT junction temperature, achieving a low RMSE value of 0.1034 ℃. This significantly surpasses existing technologies and provides robust support for temperature management in wind power converters. Furthermore, to verify the performance of the DMOA-ELM in practical application scenarios, IGBT accelerated ageing experiments were conducted, yielding a comprehensive validation dataset. The high accuracy and effectiveness of the IDMOA-ELM were confirmed through comparative analysis with experimental data, enhancing the credibility of the research. This study achieved non-destructive and high-precision prediction of IGBT junction temperature in wind power converters and significantly improving the reliability of wind power converters.